Aggressive angiomyxoma of the vulva - A rare entity - Archana Shivamurthy; Padmapriya Jaiprakash; Paramasivam Lavanya (Our Dermatology Online, 2016)
Aggressive angiomyxoma (AA) is a rare locally invasive soft tissue tumor that is known for its local recurrence. It affects women of reproductive age group. Clinically it presents as a pedunculated polyp or a polypoidal mass usually involving the pelvis, vulva, vagina and the urinary bladder. Excision is the treatment of choice. Due to its tendency for local recurrence long term follow up is adviced. We present AA in a 43year old woman involving the vulva.